The effect of giving murottal therapy combination of breathing excercise on pain levels in post sectio caesarea patients: A pre-experimental study - Amroni, Desi (Science Center Group, 2025)
Background: Postoperative pain following cesarean section is a common clinical problem that may affect maternal recovery and patient comfort. Complementary approaches such as spiritual therapy and relaxation techniques are increasingly used as supportive interventions in pain management. Objective: This study aimed to analyze the effect of murottal therapy combined with breathing exercises on pain levels among post-cesarean section patients. Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted among 40 post-cesarean section patients selected through purposive sampling. The intervention consisted of listening to the recitation of Surah Ar-Rahman for 15 minutes combined with guided breathing exercises delivered three times within one day. Pain levels were measured using the Numeric Rating Scale before and after the intervention. Data were analyzed using paired t-test analysis. Results: The mean pain score decreased from 4.95 ± 0.78 before the intervention to 2.57 ± 0.71 after the intervention. Statistical analysis indicated a significant reduction in pain levels following the intervention (p < 0.001). Conclusion: The combination of murottal therapy and breathing exercises effectively reduces postoperative pain in cesarean section patients and may serve as a complementary intervention in nursing practice.